Systemic Response to Infection Induces Long-Term Cognitive Decline: Neuroinflammation and Oxidative Stress as Therapeutical Targets - Reis, Patricia Alves; Castro-Faria-Neto, Hugo Caire (Frontiers in Neuroscience, 2022)
In response to pathogens or damage signs, immune system is activated in order to eliminate the noxious stimuli. When immune response assumes systemic conditions, including cytokine storm, vascular dysfunction and coagulopathy, multiple organ dysfunction can occur. Central nervous system is one of the major organs affected and symptoms as sickness behavior (depression, fever, among others), or even delirium can be observed due to activation of endothelial and glial cells, leading to neuroinflammation. Several reports have been shown that, due to central nervous system alterations caused by neuroinflammation, some sequels can be developed in special cognitive decline. There still not any treatment to avoid cognitive damage, especially those ones developed due to systemic infectious diseases, but preclinical and clinical trials has pointing controlling neuroinflammatory events to avoid the development of this sequel. In this minireview, we point to possible therapeutical targets and strategies to treat this sequel that has been observed as consequent of several infectious diseases, as malaria and sepsis, and recently, in consequence of the new SARS-Cov2.